The effects of glossing on incidental vocabulary learning during second language reading: based on an eye‐tracking study. (27th August 2020) - Ouyang, Jinghui; Huang, Lingshan; Jiang, Jingyang
Abstract : Providing glosses that explain the meanings of unknown words is a common method of promoting learners' learning of new words. Numerous studies have shown that compared with no‐gloss condition, glosses benefit the learning of the meaning of new words. This study combines both online (i.e., eye‐tracking) and offline (i.e., immediate vocabulary tests) measures to investigate the influences of glosses on incidental vocabulary learning and evaluating the degree to which glossing influences reading behaviour during second language (L2) reading. The eye movements of 45 high‐intermediate adult learners of English were recorded when they read a text presented on‐screen. Two different text versions (both with 17 new words) were presented to two different groups of participants: first language (L1) textual glossed and no‐glossed. After reading, unannounced vocabulary tests were administered to gauge learners' recall and recognition of vocabulary meaning. Learners performed better in meaning recall and meaning recognition tests under L1‐glossed condition. Eye‐tracking measures of the target words were significantly different in two conditions. Eye‐tracking measures of new words and their glosses in L1‐glossed condition were significantly correlated with learners' scores of vocabulary tests. L1 glosses promote the learning of the meaning of new words in an incidental condition. The attention allocated to the new words is different in L1‐glossed and no‐glossed conditions. More importantly, there is a relationship between the online reading behaviour and the vocabulary test performance in gloss condition.